Correlation of quantitative diffusion‐weighted and dynamic contrast‐enhanced MRI parameters with prognostic factors in prostate cancer. Issue 5 (5th September 2014) - Chung, Melody P.; Margolis, Dan; Mesko, Shane; Wang, Jason; Kupelian, Patrick; Kamrava, Mitchell
Abstract Introduction The aim of this study was to determine if correlations exist between quantitative parameters from dynamic contrast‐enhanced (DCE) and diffusion‐weighted (DW) MRI with National Comprehensive Cancer Network (NCCN) risk group, Gleason score (GS), maximum tumour diameter (MTD), pre‐treatment prostate‐specific antigen (PSA), clinical T stage and MRI prostate volume in prostate cancer. Method We retrospectively reviewed 3T multiparametric MRI reports on biopsy‐proven prostate cancer patients performed during radiation treatment evaluation or an active surveillance protocol. DCE‐MRI parameters included Ktrans (influx volume transfer coefficient), Kep (efflux reflux rate constant) and iAUC (initial area under the curve). Average DCE and apparent diffusion coefficient (ADC) values were recorded for regions of interest on DW‐MRI. Relationships between MRI metrics and risk group, GS, MTD, PSA, clinical T stage and MRI prostate volume were examined using analysis of variance. Central and peripheral tumours were also analysed separately in a sub‐analysis. Statistical significance was defined as P < 0.0125. Results Of 58 patients, 29%, 52% and 19% had low (L), intermediate (I), or high (H) NCCN risk disease, respectively. Ktrans significantly correlated with PSA. For central tumours, Ktrans significantly correlated with MTD and PSA, and Kep significantly correlated with PSA. For peripheral tumours, iAUC was significantly different when stratified by L/I/H risk and GS, and ADC score with L/I/H risk, GS, and clinical T stage. Conclusions DCE‐ and DW‐MRI metrics correlate with some risk stratification factors in prostate cancer. Further work is required to determine if MRI metrics are complementary or independent prognostic factors.